HIV-associated lymphoma: A 5-year clinicopathologic study from India - Rajalakshmi Sampath; Marie Therese Manipadam; Sheila Nair; Auro Viswabandya; Anand Zachariah (Wolters Kluwer Medknow Publications, 2019)
Context: Relative risk of non-Hodgkin lymphoma (NHL) in people living with HIV is 60-200 times that of normal population. This is the largest series from India on lymphomas arising in HIV-infected individuals including workup for Epstein-Barr virus (EBV) and human herpesvirus-8 (HHV-8). Aims: This study aims to ascertain the distribution and detailed clinicopathologic features of lymphoma arising in HIV-infected persons in India. Settings and Design: The study was done during the period of 2007-2011 in the pathology department of a tertiary care center in South India. Subjects and Methods: All cases diagnosed as lymphoma in the department of pathology during the study period were identified, and patients with HIV positive by serology were included in the study. Clinical details were obtained from electronic records, slides were reviewed and tissue blocks retrieved, and immunohistochemistry for HHV-8 and in situ hybridization for EBV-encoded RNA was done. Statistical Analysis Used: Descriptive statistics were done using SPSS software. Kaplan-Meier curves were used to do survival analysis. Results: Of 3346 patients diagnosed with lymphoma, 73 (2%) were diagnosed to be positive for HIV. About 87.6% of the cases were NHL, of which diffuse large B-cell lymphoma was the most common and plasmablastic lymphoma was the second common subtype. Survival was uniformly poor in 36% of the cases where follow-up was available. Conclusions: The striking differences from world literature included higher frequency of plasmablastic lymphomas, lack of primary central nervous system lymphomas, and low association with HHV8.